Fluid inclusion and stable isotopic studies of thermochemical sulfate reduction: Upper permian and lower triassic gasfields, northeast Sichuan Basin, China. (1st February 2019) - Li, Kaikai; George, Simon C.; Cai, Chunfang; Gong, Se; Sestak, Stephen; Armand, Stephane; Zhang, Xuefeng
Abstract: Fluid inclusions hosted in different stages of TSR-derived diagenetic minerals are expected to record compositions and isotopes of paleo-fluids at the time of trapping during different TSR extents. Here we report the first set of data on carbon isotopes of CH4 and CO2 and hydrogen isotopes of H2 O trapped in fluid inclusions in TSR calcites. We find that the NE Sichuan sour dolostones have initially experienced oil- and wet gas-dominated TSR, as recorded in H2 S-bearing oil inclusions with lower homogenization temperatures ( T h ) values (e.g., ≤137 °C) and the coexistence of C2+ hydrocarbon gas and H2 S in fluid inclusions. The subsequent dry gas-dominated TSR occurred in higher reservoir temperatures (> about 161.5 °C) when most C2+ hydrocarbons were exhausted. The three-stage TSR resulted in CH4 δ 13 C values becoming progressively heavier from −46.7‰ to −29.6‰, H2 O δ 2 H values shifting negatively from −36.4‰ to −67.8‰ and salinities decreasing to as low as 0.9 wt% NaCl. The dry gas-dominated TSR reaction seems to be the most efficient at water production, which, however, was limited by available reactive sulfate, and shows significant differences within the reef and shoal reservoirs along the platform margin, and the anhydrite-bearing reservoirs in the paleo-lagoon area. The TSR reaction within the porous shelf-margin reservoirs is capable of causing carbonate dissolution owing to high porosity and good connectivity of the micropore network and the resulting mass transport away from TSR sites. This resulted in CO2 δ 13 C positive shift from −9.3‰ to +6.3‰, and a positive correlation of this parameter with T h . In contrast, in the tight anhydrite-bearing reservoirs, slow mass transport and quick saturation of calcium and dissolved CO2 in the pore waters is expected to precipitate TSR calcite near the anhydrite crystals, resulting in calcite crystals having more depleted δ 13 C values (−1.4‰ to −18.9‰). This study shows that there are essential differences in the process and effects of TSR reaction due to geological differences in the settings of TSR sites.